Effect of iodine deficiency on mental and cognitive development and achievement of secondary school students in Nyala city - Bishara, Iman Abdul Rasoul Muhammad; Muhammad, Afaf Muhammad Okasha; Al-Zaila'i, Khadija Muhammad Ahmad Dafallah (Journal of Educational and Psychological Sciences, 2018)
This study addressed the subject of the effect of iodine deficiency on the mental development of the cognitive and educational achievement of a sample of secondary school students in Nyala. This study was conducted to investigate the effect of hypothyroidism on both cognitive development and learning achievement. The research community included students and students affected and not affected by the lack of iodine in the second grade secondary. The researchers selected a sample of (720) students from six schools in Nyala, (100) students in the randomized, randomized way, and their homogeneity in terms of class and age. The tools used in this study were the thyroid inflation index, TSH (T4, T3) and the study achievement test by the end of the academic year for the sample members. After the criteria were applied, the researchers analyzed the data using the SPSS test. After processing the data statistically, the search revealed the following results: There were statistically significant differences in the scores between students affected and not affected by iodine deficiency, and these differences for the benefit of those who are not affected. There was a statistically significant interaction between the iodine deficiency variable and the gender variable in favor of males, and the results showed that there was no statistically significant interaction between the type variable and the collection. The study revealed a statistically significant correlation between iodine deficiency and cognitive development and secondary school achievement. Based on the results revealed by the study, the researcher concluded: iodine deficiency leads to delays in the growth of body and mind and difficulty in academic achievement. And poor mental function is considered a return of iodine deficiency. Iodine deficiency in soil, water and food is one of the main causes of hypothyroidism. Thyroid disease is more common among students compared to students with hyperthyroidism in adulthood. In the light of these results, the researchers made some recommendations, while making proposals for future studies. The most important of which is the necessity of having a psychologist and social counselor and a specialist doctor to follow the cases of the health students to provide their educational development requirements by providing awareness programs, guidance and treatment permanently to achieve cognitive growth in the field of learning.